Aphrodite's daughters : three modernist poets of the Harlem Renaissance - Honey, Maureen, 1945- (Rutgers University Press, 2016)
"Aphrodite's Daughters brings to dramatic life three lyrical poets of the Harlem Renaissance whose work was among the earliest to display erotic passion as a source of empowerment for women. Angelina Weld Grimke, Gwendolyn B. Bennett, and Mae V. Cowdery are framed as bold pioneers whose verse opened new frontiers into women's sexuality at the dawn of a new century. Honey describes Grimke construction of a Sapphic deity inspiring acolytes to express forbidden same-sex desire while she outlines Bennett's exploration of sexual pleasure and pain and Cowdery's frank depiction of bisexual erotics. Grimke, Bennett, and Cowdery, she argues, embraced the lyric "I" as an expression of their modernity as artists, women, and participants in the New Negro Movement by highlighting the female body as a primary source of meaning, strength and transcendence. Honey juxtaposes each poet's creative work against her life writing, personal archive, and appearances in the black press. These new source materials dramatically illuminate verse that has largely appeared without its biographical context or modernist roots. Honey's highly nuanced bio-critical portraits of this unique cadre of New Negro poets reveal the fascinating complexity of their private lives, and she creates absorbing narratives for all three as they experienced sexual awakening in lesbian, heterosexual, and bisexual contexts. The vivid interplay between intimate, racial and artistic currents in their lives makes Aphrodite's Daughters a compelling story of three courageous women who dared to be sexually alive New Negro artists paving the way toward our own era."-- Provided by publisher
Keywords: Cowdery, Mae V. -- (Mae Virginia), -- approximately 1909-1953 -- Criticism and interpretation.; Bennett, Gwendolyn, -- 1902-1981 -- Criticism and interpretation.; Grimké, Angelina Weld, -- 1880-1958 -- Criticism and interpretation.; Bennett, Gwendolyn, -- 1902-1981; Cowdery, Mae V. -- (Mae Virginia), -- approximately 1909-1953; Grimké, Angelina Weld, -- 1880-1958; African American arts -- New York (State) -- New York -- 20th century.; Modernism (Literature) -- New York (State) -- New York.; African American women -- New York (State) -- New York -- Intellectual life.; Women poets, American -- 20th century.; African American poets -- 20th century.; Harlem Renaissance.; American poetry -- Women authors -- History and criticism.; American poetry -- African American authors -- History and criticism.; Arts noirs américains -- New York (État) -- New York -- 20e siècle.; Modernisme (Littérature) -- New York (État) -- New York.; Noires américaines -- New York (État) -- New York -- Vie intellectuelle.; Poétesses américaines -- 20e siècle.; Poètes noirs américains -- 20e siècle.; Poésie américaine -- Auteurs noirs américains -- Histoire et critique.; HISTORY -- United States -- 20th century.; LITERARY CRITICISM -- Women Authors.; LITERARY CRITICISM -- Poetry.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies.; SOCIAL SCIENCE -- Women's Studies.; LITERARY CRITICISM -- American -- African American.; BIOGRAPHY & AUTOBIOGRAPHY -- Women.; African American arts; African American poets; African American women -- Intellectual life; American poetry -- African American authors; American poetry -- Women authors; Harlem Renaissance; Modernism (Literature); Women poets, American; New York (State) -- New York; 1900-1999; Criticism, interpretation, etc.